PENGARUH APLIKASI YOUTUBE KIDS DALAM MENINGKATKAN AKHLAK (MORAL) ANAK USIA 5-6 TAHUN - Br Ginting, Ica Bella (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2023)
This study is to determine the effect of using the YouTube Kids application in improving the morals (morality) of children aged 5-6 years in TK IT El-Azzam, Kec. Payung Sekaki, Pekanbaru. This type of research is a quantitative quasi-experimental model. The population of this study were all children aged 5-6 years in grades B1 and B2 in TK IT El-Azzam, Kec. Payung Sekaki, Pekanbaru totaled 30 children. Determining the sample of this study using a total sampling technique, namely the technique of determining the sample by taking the entire population. So that the sample in this study consisted of 2 classes with a total of 30 children. Based on the results of research and data analysis, it can be concluded: The use of the YouTube Kids application has an effect on improving the morals (morality) of children aged 5-6 years in TK IT El-Azzam, this is proven by the results of t count > t table, (5,878> 1,796) and significance < 0.05 (0.000 < 0.05), then Ho is rejected, Ha is accepted and the dominance of development is in the BSH category (Developing as expected).